Standardization of Procedures to Contain Cost and Reduce Variability of Care After the Pandemic - Raveglia, Federico; Orlandi, Riccardo; Rimessi, Arianna; Minervini, Fabrizio; Cioffi, Ugo; De Simone, Matilde; Guttadauro, Angelo; Scarci, Marco (Frontiers in Surgery, 2021)
The COVID-19 pandemic has changed many aspects of our private and professional routine. In particular, the lockdowns have severely affected the entire health care system and hospital activities, forcing it to rethink the protocols in force. We suggest that this scenario, in spite of the new challenges involving already complex healthcare providers, may lead to the unique opportunity to rethink pathways and management of patients. Indeed, having to resume institutional activity after a long interruption that has completely canceled the previously existing schemes, healthcare providers have the unique opportunity to overcome obsolete and “we have always done in this way” model on the wave of the general desire to resume normal life. Furthermore, the pandemic has highlighted some flaws in our health system, highlighting those critical issues that most need to be addressed. This article is a review of pre-pandemic literature addressing the use of Lean Six Sigma LSS and standardization processes in thoracic surgery to improve efficiency. Our goal is to identify the main issues that could be successfully improved along the patient's entire pathway from the first referral, to diagnosis, hospitalization and surgical operation up to convalescence. Furthermore, we aim to identify the standardization processes that have been implemented to achieve significant improvements in patient outcomes while reducing costs. The methods and goals that could be used in the near future to modernize our healthcare systems are drawn up from a careful reading and interpretation in light of the pandemic of the most significant articles in the literature